PENGARUH INOVASI TEKNOLOGI DAN PENGGUNAAN INPUT TERHADAP PRODUKTIVITAS KELAPA SAWIT DI PROVINSI KALIMANTAN BARAT / Influence of Technological Innovation and Use of Production Input on Productivity of Oil Palm in West Kalimantan Province - I Ketut Ardana; Ketut Kariyasa (Jurnal Penelitian Tanaman Industri, 2016)
Indonesian government within the framework of the Master Plan for the Acceleration and Expansion of Indonesian Economic Development (MP3EI) have established oil palm as the main commodity to be developed in the so-called corridor of Kalimantan. This is mainly due to the commodity role as Indonesia's main export commodities as well as the tipping point of regional economic development in ensuring the welfare of local farmers in a sustainable manner. West Kalimantan is one of the centers of the development of oil palm in Kalimantan, after Central Kalimantan. This study aimed to analyze the role of the superior technology and use of production inputs to improve the productivity of oil palm and the factors that influence the adoption of new technologies at the farm level. Results of decomposition analysis of productivity showed that the productivity of oil palm plantations increased by 45.59%. The role of the difference in the applied technology is 22.62% and 22.97% came from the difference in input use. Quality of seeds available/planted by farmers contributed significantly to the level of productivity. Adequate provision of improved seed policies must be the top priority in efforts to improve the productivity of oil palm in the future. The policy needs to be accompanied by quality control and distribution of improved seed is strictly and continuously. The next priority policies should be aimed at encouraging farmers to use production inputs as recommended . In order for the policy to be effective, it needs to be supported by the trading system improvements to ensure the feasibility of palm oil prices at the farm level.Keywords: oil palm, decomposition of productivity, innovation, production inputs AbstrakPemerintah Indonesia dalam kerangka Masterplan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia (MP3EI) telah menetapkan komoditas kelapa sawit sebagai komoditas utama untuk lebih dikembangkan di wilayah Kalimantan Barat atau disebut koridor Kalimantan. Hal ini terutama disebabkan oleh peran komoditas ini sebagai komoditas ekspor utama Indonesia dan sekaligus sebagai titik ungkit pembangunan ekonomi daerah dalam menjamin peningkatan kesejahteraan petani setempat secara berkelanjutan. Kalimantan Barat merupakan salah satu sentra pengembangan kelapa sawit di Kalimantan, setelah Kalimantan Tengah, oleh sebab itu penelitian dilaksanakan di Kalimantan Barat pada tahun 2013. Penelitian ini bertujuan menganalisis peran teknologi unggulan dan penggunaan input produksi terhadap perbaikan produktivitas kelapa sawit dan faktor-faktor yang mempengaruhi adopsi teknologi baru di tingkat petani. Hasil analisis dekomposisi produktivitas menunjukkan bahwa penggunaan teknologi unggulan (karakterisik teknologi unggulan perbaikan manajemen produksi, serta penggunanan input sesuai anjuran) menyebabkan produktivitas kelapa sawit meningkat sebesar 45,59%. Dari peningkatan tersebut, sebesar 22,62% bersumber dari adanya perbedaan teknologi yang diterapkan dan 22,97% bersumber dari adanya perbedaan penggunaan input. Kualitas benih yang tersedia/ditanam petani memberikan kontribusi nyata terhadap tingkat produktivitas. Dalam upaya meningkatkan produktivitas sawit, maka penyediaan benih unggul yang memadai harus menjadi kebijakan prioritas utama dalam pengembangan kebun sawit ke depan. Kebijakan prioritas berikutnya dapat ditujukan untuk mendorong petani agar menggunakan input produksi sesuai anjuran. Kebijakan ini tentunya akan efektif jika pada saat yang sama petani juga memperoleh harga sawit yang layak.Kata kunci: kelapa sawit, dekomposisi produktivitas, inovasi, input produksi